Implementasi Kurikulum Merdeka Belajar untuk Meningkatkan Minat Belajar Siswa Kelas X di SMA Katolik Seminari Santo Fransiskus Xaverius Kakaskasen - Christofora Dominika Kalele; Fecky Evendy Singal; Marthinus Marcel Lintong (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2024)
Interest in learning is one of the main things that can support the learning process. In fact, there are still many students who feel bored with learning and are bored because the way of learning is still conventional. This relates to the curriculum used by schools because one of the supporting factors for increasing student interest in learning is the curriculum. This research was conducted at St. Francis Xavier Seminary Kakaskasen High School, to find out how the implementation of the Free Learning Curriculum for Increasing Student Interest in Class X, supporting and inhibiting factors and efforts to increase student learning interest in implementing the Free Learning Curriculum. The type of method used is a descriptive qualitative method. The research results obtained are that the Free Learning Curriculum has been implemented in the Catholic High School Seminary of St. Francis Xavier Kakaskasen. In addition, there are supporting factors such as availability platform independent teaching, the existence of IHT activities or outreach, and inhibiting factors such as lack of internet access and computer room and inadequate infrastructure. As for the efforts made by the school, namely carrying out mock study activities for teachers at SMA N 8 Manado, teachers must be more creative in the learning process, and regarding the provision of infrastructure. Thus conclusions can be drawn including: First, the Free Learning Curriculum has been implemented in Seminary High Schools which is marked by the existence of the Pancasila Student Profile Strengthening Project activity. Second, there are factors that influence the implementation of the Independent Learning Curriculum for the sake of increasing student learning interest which are described in supporting and inhibiting factors. Third, the efforts made by the school are carrying out replicated studies at other schools regarding the Free Learning Curriculum, the way teachers create fun learning, and the provision of supportive school facilities.